A Comparative Study between Extrovert and Introvert Personality on Speaking Achievement - Sinta Dewi Anggraeni; Semi Sukarni; Ismawati Ike Nugraeni (Department of English Language Education, Universitas Muhammadiyah Purworejo, Indonesia, 2022)
The research's goals are to compare speaking achievement between extrovert and introvert personalities, and to see if there is a significant difference in speaking achievement between extrovert and introvert personality on the tenth grade at Senior High School 1 Pejagoan in the academic year 2020/2021. This study is classified as quantitative research with a non-experimental design. The population of this study is the tenth-grade students of SMA N 1 Pejagoan in the academic year 2020/2021. The researcher used a purposive selection strategy to select 60 students as her sample. The data was collected using a questionnaire, and the teacher provided the researchers with a copy of the student's speaking achievement as a document. There are 24 Yes/No questions in the form. To answer the issue and hypothesis statements, descriptive and inferential analysis techniques are used to analyze the data. The results of this study demonstrate that extrovert students' speaking achievement is in the